Analysis of The Synergity of School-Based Management and Project-Based Learning Models on Learning Outcomes at Kartika High School Ambon - Abednego, Abednego; Noya, Ferdinanda S. (Balitbangda Provinsi Lampung, 2018)
This study endeavors to achieve two primary objectives: firstly, to enhance the understanding of sociology, particularly focusing on the concept of social change, by integrating the principles of school-based management and employing the project-based learning model within the high school setting. Secondly, to investigate the substantial causal connection between the amalgamation of school-based management and the project-based learning model in high school environments. Employing a quasi-experimental research design, the study involved 60 students from the eleventh-grade Science class at SMA Kartika Ambon. The findings demonstrate a notable improvement in sociological learning outcomes related to social problems through the collaborative application of school-based management and project-based learning at Ambon City High School. Statistical analyses reveal a significant disparity in learning outcomes between the experimental and control groups, with the experimental group showcasing a substantial increase in scores. Additionally, the study identifies a robust correlation between the synergy of school-based management and the project-based learning model, indicating their simultaneous impact on sociology learning outcomes. Nonetheless, the generalizability of these findings is constrained by the study's focus on a single high school in Ambon City, underscoring the necessity for future research endeavors encompassing a broader subject pool.